Gratitude Journaling Practices Influences Positive Affect among Early Adolescents: A Study among Junior High School Students in a Rural Area Rancaekek Indonesia - Karinta Elmira Amalia; Pinasthika Kautsari Pradipta; Dhia Nada Aldilla; Wilis Srisayekti; Yanti Rubiyanti; Chandra Yudistira Purnama (Universitas PGRI Yogyakarta, 2026)
Adolescence is a developmental stage marked by heightened emotional vulnerability, making school-based interventions essential for promoting well-being. This study examined the effects of a structured gratitude journaling program on positive affect among junior-high-school students in a rural area, Rancaekek, Bandung Regency, Indonesia. Using a pretest–posttest control group design, 70 students (aged 13–15) were randomly assigned to an experimental group (35 students) or a control group (35 students). Positive affect was measured at three time points using the Indonesian version of the PANAS-C. Mixed ANOVA results showed a significant interaction effect, with the experimental group reporting greater improvements in positive affect compared to controls (p = .001, η² = .131). Qualitative reflections supported these findings, where students expressed greater emotional awareness, social connection, and positive self-perception. The study concludes that gratitude journaling is a low-cost, evidence-based strategy for enhancing adolescent emotional well-being. School-based interventions could be developed based on these results. Keywords: gratitude journaling, school-based intervention, positive affect, adolescents, positive psychology